Konsep Kurikulum SMPS Merdeka Tampor Paloh Yang Memerdekan Peserta Didik - Yusba, Yusba Alhamda Syari; Asrul, Asrul (Program Pascasarjana IAIN Langsa, 2023)
SMPS Merdeka Tampor Paloh is a junior high school in Simpang Jernih District, East Aceh Regency, which was founded in 2007, where the learning process is sometimes carried out on riverbanks, under large trees, and on hillsides according to the theme or topic used as learning material at the time. That's with makeshift stationery. This study was carried out with the aim of knowing and describing the SMPS Merdeka curriculum concept, learning model, and evaluation. This research uses a descriptive qualitative research approach using interview and documentation instruments. The results of the research explain that the curriculum concept applied is the natural curriculum and the environment around which they live, which makes their students very active, participative, and communicative. The learning model and evaluation applied are direct learning, problem-based learning, and project-based learning, so the evaluation is also direct, namely in the form of presentations and workshops.